A digital infrastructure for integrating decentralized assets into redispatch. Decentralized Redispatch (DEER): Interfaces for providing flexibility - Marc-Fabian Körner; Lars Nolting; Matthias Babel; Marvin Ehaus; Paula Heeß; Jonathan Lautenschlager; Malin Radtke; Leo Schick; Jens Strüker; Stefanie Wiedemann; Till Zwede (Universität Bayreuth, Lehrstuhl für Wirtschaftsinformatik, 2025)
In response to the challenges posed by an increasingly decentralized energy system characterized by a high penetration of renewable energy sources, grid operators are experiencing heightened pressure to effectively manage grid congestion. Concurrently, both the European Union as well as the German government's ambitious climate targets are fostering the proliferation of small-scale systems like heat pumps, photovoltaic systems with battery storages, and electric cars, thereby enhancing the flexibility potential for redispatch operations. The project "Decentralized Redispatch (DEER): Interfaces for providing flexibility" aims to explore the integration of decentral flexibility into congestion management practices. This White Paper provides an overview on the project's first outcomes and the necessary background technologies and methods. The project's primary focus lies in designing an architecture in the context of a multi-agentsystem that facilities secure and sovereign communication among all stakeholders in such a decentralized redispatch, ensuring data security, data privacy, and verifiability. The DEER project sets out to analyze the potential of leveraging self-sovereign identity management methods, combined with technologies such as zero-knowledge proofs and distributed ledgers, as a robust framework for achieving these objectives. – – Mit den Herausforderungen, die durch ein zunehmend dezentrales Energiesystem mit einem hohen Anteil erneuerbarer Energieanlagen entstehen, verändern sich auch die Anforderungen an das (zukünftige) Netzengpassmanagement. Gleichzeitig treiben sowohl die Europäische Union als auch die Bundesregierung für die Erreichung der Klimaschutzziele die Verbreitung von elektrifizierten Kleinstanlagen wie Wärmepumpen, Photovoltaik-Anlagen mit Heimspeichern und Elektroautos voran. Damit erhöht sich zeitgleich ein (bisher) ungenutztes Potenzial dieser Anlagen für den Redispatch. Das Projekt "Dezentraler Redispatch (DEER): Schnittstellen zur Flexibilitätsbereitstellung" zielt darauf ab, die Integration von Kleinstflexibilitäten in das Netzengpassmanagement zu erforschen. Dieses White Paper gibt ein Überblick über die ersten Projektergebnisse sowie die notwendigen Technologien und Methoden. Das Projekt konzentriert sich dabei hauptsächlich darauf, eine Architektur im Kontext eines Multi-Agenten-Systems zu entwerfen, die eine sichere und datensouveräne Kommunikation zwischen allen Stakeholdern im dezentralen Redispatch ermöglicht und damit sowohl Datenschutz als auch Verifizierbarkeit gewährleistet. Dabei zielt das DEER-Projekt darauf ab, das Potenzial von digitalen, selbstbestimmten Identitäten (SSI) in Kombination mit ZeroKnowledge-Proofs und verteilten Ledger-Technologien als geeigneten Rahmen zur Erreichung dieser Ziele zu analysieren.
urn:nbn:de:bvb:703-epub-8184-4
Keywords: 650; Redispatch; SSI; Multi-Agent Systems; Zero Knowledge Proof